2004
DOI: 10.1021/ja046304t
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of a 4-(2‘-Pyridyl)-1,2,3,5-Dithiadiazolyl Cobalt Complex

Abstract: The 4-(2'-pyridyl)-1,2,3,5-dithiadiazolyl neutral radical 1 has been prepared for use as a spin-bearing bidentate ligand. The coordination of this ligand to bis(hexafluoroacetylacetonato)cobalt affords a thermally stable complex 2. Magnetic susceptibility measurements of the crystalline complex indicate ferromagnetic coupling between the ligand-centered spin and the unpaired electrons of the high-spin Co(II).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 14 publications
(13 reference statements)
2
47
0
Order By: Relevance
“…The bidentate pyDTDA ligand was coordinated to the Co(hfac) 2 fragment and structural and magnetic properties of the sublimed, crystalline complex ( Fig. 7) were reported (where hfac = 1,1,1,5,5,5-hexafluoroacetylacetonato-) [47]. There are number of points regarding the Co(hfac) 2 (pyDTDA) complex that are worth noting.…”
Section: Transition Metal Complexesmentioning
confidence: 98%
See 2 more Smart Citations
“…The bidentate pyDTDA ligand was coordinated to the Co(hfac) 2 fragment and structural and magnetic properties of the sublimed, crystalline complex ( Fig. 7) were reported (where hfac = 1,1,1,5,5,5-hexafluoroacetylacetonato-) [47]. There are number of points regarding the Co(hfac) 2 (pyDTDA) complex that are worth noting.…”
Section: Transition Metal Complexesmentioning
confidence: 98%
“…In 2004, Preuss et al reported the first N-coordination complex of a DTDA radical [47]. The 2′-pyridyl-1,2,3,5-dithiadiazolyl radical (pyDTDA) was designed as a chelating ligand, intended to remain paramagnetic, with little disruption to the thiazyl heterocycle upon coordination.…”
Section: Ncoordination Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…The ligand 4-(2 -pyridyl)-1,2,3,5-dithiadiazolyl (pyDTDA) [142], is similar to the aforementioned verdazyl-derived ligands in terms of coordination environment and distribution of electron density on the ligand. Although the ligand composition within the molecule is identical in complexes of the type (pyDTDA)M(hfac) 2 geometries around each metal ion resulted in significantly different crystal packing.…”
Section: Verdazyl and Thiazyl Radical-containing Complexesmentioning
confidence: 99%
“…The pyDTDA ligands are N-coordinated to La(III) in a bidentate fashion (Figure 1), similar to previously reported transition metal coordination complexes of this radical ligand. [16][17][18] In both monoclinic phases (vide infra), the pyDTDA ligands are symmetry-related. Although the symmetry is lowered in the triclinic phase, the coordination geometry does not change dramatically as a function of temperature and, in all phases, it is best described as a sphenocorona, 34 typical of 10-coordinate lanthanide species.…”
Section: Structural Featuresmentioning
confidence: 99%